2010
DOI: 10.1007/s00018-010-0470-z
|View full text |Cite
|
Sign up to set email alerts
|

Sterol binding by OSBP-related protein 1L regulates late endosome motility and function

Abstract: ORP1L is an oxysterol binding homologue that regulates late endosome (LE) positioning. We show that ORP1L binds several oxysterols and cholesterol, and characterize a mutant, ORP1L Δ560-563, defective in oxysterol binding. While wild-type ORP1L clusters LE, ORP1L Δ560-563 induces LE scattering, which is reversed by disruption of the endoplasmic reticulum (ER) targeting FFAT motif, suggesting that it is due to enhanced LE-ER interactions. Endosome motility is reduced upon overexpression of ORP1L. Both wild-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
92
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 59 publications
8
92
0
Order By: Relevance
“…It is notable that this property is related to the cholesterol efflux function of apoE as using the 4F mimetic peptide elicited the same results. Although the underlying reason why GDI extraction of Rab7 is modulated by cholesterol is unknown, results from previous studies suggested that this regulation perhaps involves oxysterol-binding protein-related protein 1L through the Rab7 effector Rab7-interacting lysosomal protein (35,86,87). Whether this activity subsequently regulates the extraction of Rab7 by GDI requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…It is notable that this property is related to the cholesterol efflux function of apoE as using the 4F mimetic peptide elicited the same results. Although the underlying reason why GDI extraction of Rab7 is modulated by cholesterol is unknown, results from previous studies suggested that this regulation perhaps involves oxysterol-binding protein-related protein 1L through the Rab7 effector Rab7-interacting lysosomal protein (35,86,87). Whether this activity subsequently regulates the extraction of Rab7 by GDI requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Glued from RILP, thereby facilitating plus-end-directed transport of late endosomes by kinesin motors (Rocha et al, 2009;Vihervaara et al, 2011). The ER thus coordinates the direction of late endosomal movement, but why is the timing of this process regulated by cholesterol?…”
Section: Er In Control Of Endosomal Maturationmentioning
confidence: 99%
“…Silencing of RILP or ectopic expression of its dominant negative N-terminally truncated mutant (RILPD199) have been shown to impair endosomal maturation as well as phagosome fusion to lysosomes thereby facilitating intracellular Salmonella survival (Marsman et al, 2004;Harrison et al, 2004;Guignot et al, 2004). Dynein motor recruitment to RAB7-RILP is controlled by interactions between the cholesterol sensor ORP1L and the ER protein VAP-A and this mechanism is responsible for vesicle clustering observed in lysosomal storage diseases characterized by accumulation of cholesterol in the late endosomal compartments (Rocha et al, 2009;Vihervaara et al, 2011).…”
Section: Introductionmentioning
confidence: 99%